Pneumocephalus after semi-sitting vestibular schwannoma surgery (SSAS): a volumetric analysis of risk factors and early clinical associations - Ahmed Hafez Mousa; Boris Tufegdzic; Osama Abdullah; Massimo Lamperti; Mohamed Samy Elhammady; Florian Roser (Acta Neurochirurgica, 2026)
Abstract Objectives The semi-sitting position offers distinct microsurgical advantages for vestibular schwannoma resection but predisposes to postoperative intracranial air accumulation. While pneumocephalus is commonly regarded as an expected radiographic finding, its volumetric burden and the determinants of patient- and procedure-specific factors remain incompletely characterized. Methods We retrospectively analyzed 48 consecutive vestibular schwannoma resections performed in the semi-sitting position at a single tertiary center. Postoperative pneumocephalus. was quantified using CT-based volumetric segmentation. Air burden was analyzed both categorically (> 10 mL vs ≤ 10 mL) and continuously (log-transformed volume). Candidate predictors were assessed using univariate and multivariable Firth penalized logistic regression, complemented by robust linear regression to evaluate continuous dose–response relationships. Collinearity was formally assessed prior to multivariable modeling. Results High postoperative pneumocephalus (> 10 mL) occurred in 12.5% of patients. In multivariable analysis, higher body mass index (adjusted OR 1.12 per kg/m 2 ), male sex (OR 3.21), longer operative duration (OR 1.28 per hour), and larger axial tumor size (OR 1.29 per 5 mm) independently predicted high air volume. Continuous modeling demonstrated concordant dose–response relationships for the same variables (all p < 0.05). Increasing intracranial air volume was associated with higher odds of early postoperative complications (OR 1.77 per mL, 95% CI 1.02–3.05). Significant venous air embolism occurred in 14.5% of patients, and no pulmonary air embolism was observed. Conclusions Postoperative intracranial air accumulation following semisitting vestibular schwannoma surgery is common and quantifiable. Male sex, higher BMI, longer operative duration, and larger axial tumor size consistently identify patients at increased risk for greater air burden. Intracranial air volume is associated with early postoperative morbidity and should be considered a perioperative risk marker rather than a purely incidental imaging finding. Targeted mitigation strategies in high-risk patients may help preserve the benefits of the semi-sitting approach while limiting air-related morbidity.